Dynamic Analysis of the Nonlinear Relationship Between Key Metal Prices and New Energy Vehicle Market - Li, Jiaming (Transactions on Social Science, Education and Humanities Research, 2024)
Up against the global energy transformation, the new energy vehicle industry has been in a stage of rapid development. Key metals represented by nickel are indispensable raw materials supporting the new energy vehicle industry, with their price fluctuations influencing its development, thereby affecting the global energy transformation. Studying the dynamic nonlinear relationship between the price fluctuation of the nickel as the key metal and the new energy vehicle market will provide a new perspective for understanding the dynamic development of the new energy vehicle market. Based on nickel price data, new energy vehicle market index, combined with Markov vector autoregressive model and cumulative impulse response function, this paper conducts research on the impact of nickel price fluctuations on the new energy vehicle market. According to the empirical results, the impact of nickel price fluctuations on the new energy vehicle market is different under various regimes. During the low-speed and high-speed development periods, nickel price fluctuations have a negative impact on the new energy vehicle market. During the stable development period, nickel price fluctuations mainly have a positive impact on the new energy vehicle market. Based on the above conclusions, this paper proposes policy suggestions for the relevant subjects.